Voltammetry at electrodes decorated with an insulating porous film: Understanding the effects of adsorption - Chan, HTH; Kätelhön, E; Compton, RG (Elsevier, 2017)
Recent literature has evinced a keen interest in porous electrodes. Numerous applications have been discussed and some aspects of the voltammetry investigated, a theoretical description of adsorption- and desorption processes though remains largely absent. The present study fills this important gap and provides a detailed analysis of the impact of adsorption on voltammetric electrode responses in porous materials. It is shown that in some cases, adsorption- and desorption processes may aid the detection of analytes while in other cases a planar unmodified electrode is superior in performance. Finally practical conclusions are drawn for the design of future experimental systems.